Using Virtual Reality in blood grouping training - Ayesha Naeem, Alison Hines (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Alison Hines is a clinical training and educational manager who is currently working with the NHS Blood & Transplant department in Filton (Bristol). NHS Blood Transplant has recently introduced a VR (Virtual Reality) training programme that enhances knowledge on blood transfusion education2. This program can be accessed on the Meta Quest APP Lab store. The NHSBT blood identification app gives learners an insight into the processes of correct blood group and educates them on the consequences of administering a transfusion following incorrect blood group identification. In addition to realistic simulations that highlight the grave consequences of mistakes, it also provides quick feedback. This app aims to provide an immersive hands-on learning experience as well as raises awareness of transfusion science encouraging recruitment in this field to help overcome staffing shortages in transfusion laboratories. The Editorial Team would like to thank Alison for her time and contributions to this article.